Novel Use of a Custom Fixation Plate in Pediatric Fibrous Dysplasia - Patrick W. Harbour, MD; Karina Charipova, BS; Danielle Dang, MD; Leon Moores, MD; Stephen B. Baker, MD, DDS (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary. The authors present a case of a 11-year-old girl with fibrous dysplasia involving the nasal cavity and sphenoid sinus that potentially required a tracheostomy for anesthesia. The tumor was to be approached through both supraorbital and Le Fort I osteotomies. The tumor prevented nasal intubation, and the necessity of maxillomandibular fixation to reduce the osteotomized maxilla with traditional fixation prevented oral intubation. Given the age of the patient and the desire to avoid a tracheostomy scar, a decision was made to utilize custom fixation plates. Virtual surgical planning was utilized to design custom cutting guides with splints for maxillomandibular fixation. These custom maxillary orthognathic plates ensured accurate reduction of the osteotomized maxillary segment and allowed for placement of an oral endotracheal tube. Despite the oral endotracheal tube preventing maxillomandibular fixation, use of custom plates established proper occlusion as determined immediately after extubation and at postoperative visits.